Digital cultural intelligence and its role in enhancing expatriate work adjustment: A configurational approach in global work environments - Fatimah Mahdy; Faiz Binzafrah; Osman Elsawy (PLoS ONE, 2026)
This study investigates how the digital dimensions of cultural intelligence influence expatriates’ work adjustment across the Gulf Cooperation Council countries. Adopting a neo-configurational perspective, it explores four facets of digital cultural intelligence alongside contextual factors such as perceived organizational support, international experience, language proficiency, and digital-cultural training. Data from 208 expatriates working in tourism, healthcare, and higher education in Saudi Arabia, the UAE, Oman, and Qatar reveal multiple equifinal pathways to successful adjustment. Results highlight that adaptation emerges from distinct combinations of digital, cultural, and organizational factors rather than a single determinant. Two dominant configurations drive adjustment: high metacognitive and behavioral intelligence, combined with strong organizational support, and cognitive-motivational intelligence, paired with language skills and training to compensate for limited international experience. The study advances the person–environment fit theory by introducing the concept of digital–cultural fit and underscores the value of configurational methods in global HRM research.